2006
DOI: 10.1002/jcp.20574
|View full text |Cite
|
Sign up to set email alerts
|

SEL1L a multifaceted protein playing a role in tumor progression

Abstract: Since the cloning in 1997 of SEL1L, the human ortholog of the sel-1 gene of C. elegans, most studies have focused on its role in cancer progression and have provided significant evidences to link its increased expression to a decrease in tumor aggressiveness. SEL1L resides on a ''Genome Desert area'' on chromosome 14q24.3-31 and is highly conserved in evolution. The function of the SEL1L encoded protein is still very elusive although, several evidences from lower organisms indicate that it plays a major role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 92 publications
7
46
0
Order By: Relevance
“…Nevertheless, it is possible the partial SEL1L peptide has other cellular function(s). Additionally, the mammalian Sel1l gene expresses multiple transcripts derived through alternative splicing among exons in the 5Ј and 3Ј ends of the gene (27). Indeed, our Northern analysis has detected at least two smaller transcripts in the mutant embryos.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Nevertheless, it is possible the partial SEL1L peptide has other cellular function(s). Additionally, the mammalian Sel1l gene expresses multiple transcripts derived through alternative splicing among exons in the 5Ј and 3Ј ends of the gene (27). Indeed, our Northern analysis has detected at least two smaller transcripts in the mutant embryos.…”
Section: Discussionmentioning
confidence: 72%
“…Activated ATF6 translocates to the nucleus where it binds to the ER stress responsive element in genes encoding ER chaperone proteins (25,26). SEL1L (suppressor enhancer Lin12 1 like) is a widely expressed ER membrane protein (type I) with a complex domain structure (27). Biochemical and molecular studies in vitro revealed that in eukaryotic cells SEL1L nucleates an ER membrane protein complex that is required for dislocation of unfolded or misfolded proteins from the ER lumen into the cytosol for degradation (28 -33).…”
Section: The Endoplasmic Reticulum (Er)mentioning
confidence: 99%
“…Nonetheless, studies have implicated Sel1L in various cellular processes, including tumorigenesis of various cancer types (31), stem cell differentiation (32), pancreatic epithelial cell differentiation (33), and retrotranslocation of cholera toxin to the cytosol (26). Variants in the Sel1L gene have been identified in human patients with autoimmune thyroid diseases (34), in canines with progressive early-onset cerebellar ataxia (35), and in humans with Alzheimer's disease (36).…”
Section: Significancementioning
confidence: 99%
“…Here we explore the potential therapeutic advantages of VPA treatment combined with perturbation of the proteostasis network on GSC by targeting SEL1L, a crucial modulator of homeostasis (15)(16)(17)43) and linked to neural stemness maintenance and lineage determination (18) as well as cancer aggressiveness (19,21,43).…”
Section: Discussionmentioning
confidence: 99%